A Pragmatic Analysis Of Directions In Cosmetics Product Labels - PURWANINGSIH, TYAS (2012)
This research deals with directions in cosmetics product labels. The aims of the research are identifying the reconstructed forms and describing the meaning of the directions in cosmetics product labels. The type of this research is qualitative study with the approach pragmatics. This research has data source from cosmetics product labels. The method of collecting data is documentation and the steps are reading, classifying, and coding the data. The technique of analyzing data are identifying the reconstructed forms of directions in cosmetics product labels by applying the kinds of sentences of Frank, and describing the meaning of directions in cosmetics product labels by applying the theory of Wijana. The method of analyzing data is descriptive technique. Having analyzed the data, the researcher found that the reconstructed forms of directions are all in imperative sentences which it divided to 70,83% of simple sentences, 18,75% of compound sentences, and 10,42% of complex sentences. There are two kinds of the meaning of the directions; they are literal speech act 91,67% and non literal speech act 8,33%.